Physics-Based Digital Twin Identifies Trade-Offs Between Drying Time, Fruit Quality, and Energy Use for Solar Drying - Prawiranto, Kevin; Carmeliet, Jan; Defraeye, Thijs (Frontiers in Sustainable Food Systems, 2021)
Solar drying is regarded as a less reliable process compared to continuous hot-air drying due to the intermittency of solar radiation. This problem is mitigated by equipping solar dryers with thermal storage, dehumidifier units, or auxiliary heating that enhances drying continuity during night time. In this study, we combine a mechanistic fruit drying model, quality models (vitamin C decay and browning reaction) and weather data to evaluate the drying characteristics and quality evolution of apple fruit with and without the aforementioned improvement strategies. By coupling to measured weather conditions, a digital twin of the drying fruit is established. The twin outputs drying times and final product quality for a specific fruit type and size, a particular dryer configuration, and specific weather conditions. The trade-offs between drying time, final product quality and energy use for the different improvement strategies of solar drying are documented. We found that solar drying may benefit from the slower drying due to the improvement of product quality. Compared to the other improvement strategies, dehumidification of the drying air is shown to be superior in retaining the vitamin C content and prohibiting the browning reaction. However, in general, drying with auxiliary heating is found to balance the trade-offs between drying time, final product quality and energy use the best, mainly since the weather-dependency of the process is mitigated. Additionally, we quantified the impact of a pre-treatment process that modifies the permeability of the fruit tissue by breaking the cell membrane. We found that inducing such lysis is more effective in decreasing the drying time when drying is conducted at low (room) temperature. This study shows that using the developed digital twin, future drying process and control strategies could be optimized in real-time for every single drying run.